Impact of board characteristics on firms’ technical efficiency of family owned and non-family owned business - Wong, Wai Wah (2020)
Family-owned business (FOB) forms the core of the economic activities in most countries. It is estimated that 65%-80% of worldwide businesses are owned by families (Gersick et al., 1997). The fact that they have been able to survive, as far as the recorded history has manifested, prove that they have the resilience to endure historical economic and political ups and downs. They have also proven that they are the master of survival as the businesses can be passed down generations after generations. To do so, these firms need to have superior firm performance to meet the families' economic demands. Past studies on firm performance were usually conducted by using Return on Asset (ROA), Return on Equity (ROE), and Tobin’s Q as proxies for firm performance, which are proven to have inconsistent results. Hence, the first objective of this research is to examine, compare and determine who is more superior based on firm efficiency (technical efficiency) as a proxy for the firm performance of both family-owned business (FOB) and non-family owned business (non-FOB). By using Data Envelopment Analysis (DEA), firms’ efficiency ratios for five ASEAN countries (Malaysia, Singapore, Indonesia, Philippines, and Thailand) are calculated and subjected to two samples t-test to determine whether FOB or non-FOB is more efficient. The second objective is to examine the influence of board characteristics (education level, experience level, composition, and size) on firm efficiency in the context of Family-Owned Business (FOB) and Non-Family Owned Business (non- FOB). Panel regression analysis is applied to test the board characteristics’ influence based on a sample of firms from five ASEAN countries. The third objective is to determine if the board experience level (EXP) is the most influential determinant and meanwhile, board size (SIZE) is the least for both FOB and non-FOB. Firms’ and countries’ data are collected for ten years period, starting from 2007 till 2016. The first stage analysis’ findings for the first objective did not document FOB is significantly more efficient than non-FOB for all the five countries. Meanwhile, the second stage findings for the second objective did not document the consistent significant influence of the four board characteristics on firm efficiency for all the five countries. Although inconsistent the characteristics did influence the firms’ efficiency both positively and negatively. Hence, a more pertinent question arises, is there an optimum value or size for the board characteristics with firm efficiency? The findings also document weak evidence, EXP is the most influential board characteristics in determining firm performance. EXP is significant for FOB Philippines and Thailand. These findings are essential for the board of directors (BOD), senior management of the firms, researchers, policymakers, academics, and the general public. 1) Ceteris paribus, both FOB and non-FOB should operate at the same efficiency and ability to generate similar returns for their shareholders. Hence, the findings contribute to the debated firm efficiency in both FOB and non-FOB by providing evidence both are equally efficient in the five ASEAN countries. 2) There is no conclusive evidence documenting all the four BOD’s characteristics positively influencing the firm performance 3) provide weak evidence, EXP is the most influential board characteristic in the ASEAN region.